CANVA for math teaching - Hernández Rosales, Andrea Elizabeth; López Cevallos, Franklin Ernesto (SATHIRI, 2025)
This study, conducted at the Middle Sublevel of Unidad Educativa Hno. Miguel La Salle, aimed to investigate the impact of using the Canva platform in teaching mathematics to students with Special Educational Needs (SEN). The research involved two groups of students: an experimental group that used Canva as a pedagogical tool and a control group that followed usual pedagogical procedures. Additionally, mathematics teachers were involved and received specific training in the use of this platform. The method employed included the application of tasks designed in Canva, adapted to meet the needs of students with SEN. The tasks focused on strengthening key mathematical skills through interactive activities. The results revealed a significant improvement in the academic performance of the experimental group, with an average increase of 2 points 2. This finding suggests that the integration of Canva into the teaching-learning process not only benefits students but also promotes inclusive and effective pedagogical practices. The study emphasizes the importance of teacher training in the use of digital platforms and the implementation of adaptive pedagogical strategies, especially aimed at students with SEN in the field of mathematics.